PROKRASTINASI AKADEMIK MAHASISWA FKIP UNIVERSITAS RIAU - Tri Umari; M. Arli Rusandi; Elni Yakub (Jurnal Pendidikan, 2020)
The purpose of this study was to look at the description of academic procrastination of FKIP students at Universitas Riau. Academic procrastination is the behavior of delaying or avoiding starting to do academic work by stalling, causing discomfort. Data collection in this study was carried out using quantitative techniques through the Academic Procrastination Scale-Short Form. The results showed that students' academic procrastination was in the medium category. Even though they are in the medium category, institutions, lecturers, and students need to be more vigilant in avoiding academic procrastination behavior and avoiding the adverse effects of such behavior.